Effects of deceleration-focused exercise strategies on shoulder range of motion and throwing velocity in baseball and softball athletes - Garner, S.; Wicke, J.; Legreaux, S.; Chianchiano, B. (Sports Biomechanics, 2021)
This study examined the effects of deceleration-focused exercises on shoulder range of motion and throwing velocity in both softball and baseball players. Volunteers included 28 Division III William Paterson University baseball and softball athletes (18 females and 10 males), who were evenly distributed across two groups both undertaking 14 sessions of either resistance band or handheld medicine ball exercises (band vs. ball group). A pre-test and post-test measured participants' best active internal/external shoulder rotation and best throwing velocity at a target 40ft away. A two-tailed, independent t-test showed no significant differences in velocity, internal rotation or external rotation (p<0.01) between the band and ball groups. However, the average change in velocity in the ball group was double that of the band group (1.50±2.06 m/s versus 0.73±2.24 m/s). For change in both internal and external rotation the band group (2.86±5.27° and 3.29±3.87°, respectively) was greater than the ball mean (1.93°±3.32° and 1.29±6.52°, respectively). These findings suggest that overhead athletes aiming to increase throwing velocity can benefit from performing deceleration training with weighted balls whereas resistance bands appear to improve shoulder rotation.